High-chlorine-capacity long-service-life dechlorinating agent for dechlorinating reformed hydrogen and preparation method of dechlorinating agent
By combining modified nanocellulose-loaded activity accelerator, ultrafine crystallized molecular sieve and modified starch, high chlorine capacity, long life, low wear rate and high crush strength dehydration agents are prepared, which solves the problems of low chlorine capacity and short service life of existing dehydration agents, and significantly improves the dehydration effect and use cost.
Patent Information
- Application Number
- CN202510301352.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing solid dechlorination agents used for reforming hydrogen dechlorination have problems such as low chlorine capacity, low crushing strength, high wear rate, and short service life, resulting in unsatisfactory dehydration effect and high cost of use.
The dechlorination agent prepared by high-pressure extrusion method is used to improve the inorganic chlorine penetration capacity, crushing strength and wear resistance of the dechlorination agent.
The dehumidification effect of high chlorine capacity, long life, low wear rate and high crushing strength is achieved, which significantly improves the service life of the dehumidifier and the industrial application value.
Smart Images

Figure CN119793393A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-chlorine capacity and long-life dechlorinating agent for dechlorinating reformed hydrogen and a preparation method thereof, belonging to the technical field of dechlorination. Background Art
[0002] As one of the core processes in the petroleum refining industry, catalytic reforming has always been difficult to effectively remove inorganic chlorine. There are three main sources of hydrogen chloride and parts in the catalytic reforming unit that need to remove inorganic chlorine, namely pre-hydrogenation, reforming by-product hydrogen (referred to as reforming hydrogen) and reforming regeneration gas. Among them, the by-product reforming hydrogen has very important utilization value. It is usually sent to various hydrogen users such as hydrocracking units after compression, cooling, freezing and contact separation. Since the reforming catalyst contains chlorine, the reforming hydrogen will contain trace amounts of hydrogen chloride. Under normal circumstances, the content of hydrogen chloride is 4~6μL / L. If these trace amounts of hydrogen chloride are not dechlorinated and purified, they will directly enter the adjacent hydrorefining unit, resulting in serious problems such as salting out and equipment pipeline corrosion. Hydrogen chloride can generally be removed by chemical absorption or chemical adsorption. However, chemical absorption has many limitations in application due to its poor purification and equipment corrosion. Therefore, chemical adsorption is more commonly used in industry to remove inorganic chlorine, and solid dechlorinating agents are mostly used. However, solid dechlorinating agents currently have significant disadvantages such as low inorganic penetration chlorine capacity, low crushing strength, and poor wear resistance. As a result, there are problems such as unsatisfactory dechlorination effect and short service life, and the need for high-frequency regular replacement, which increases industrial use costs.
[0003] Chinese patent CN118491506A discloses a normal temperature dechlorinating agent for reforming hydrogen and hydrogen-containing synthesis gas and a preparation method thereof, wherein the normal temperature dechlorinating agent comprises 10% to 40% zinc oxide, 10% to 40% attapulgite, 10% to 30% light calcium carbonate, 2% to 8% zinc carbonate, 1% to 8% potassium carbonate, and 2% to 5% water glass by total weight is added to the above mixed powder; the preparation method of the present invention comprises the steps of liquid preparation, dry mixing of powder, wet mixing of mixed liquid and powder, die extrusion molding, blank curing, blank drying, blank calcination, inspection and packaging of finished dechlorinating agent, etc. The normal temperature dechlorinating agent obtained in the patent has the advantages of high crushing strength and long service life, but the maximum chlorine capacity at room temperature can only reach 31.9%, which is not particularly ideal.
[0004] Chinese patent CN118437300A discloses a dechlorinating agent and its preparation method and application, a method for removing gaseous hydrogen chloride, and a method for regenerating the dechlorinating agent. The dechlorinating agent comprises: a carrier and an active dechlorinating component loaded on the carrier, wherein the carrier is a microspherical silicon-aluminum composite material, and the active dechlorinating component is an alkali metal compound; the general formula of the microspherical silicon-aluminum composite material is Si x Al y O z, wherein 1≤x≤15, 1≤y≤4, 4≤z≤33. The dechlorination agent obtained by the patent has a relatively high chlorine capacity, but a relatively large wear index, poor wear resistance, and a difficult long service life.
[0005] From the above, we can see that the solid dechlorinating agent used for dechlorination of reforming hydrogen still has problems such as low chlorine capacity, low crushing strength, high abrasion rate and short service life. Therefore, the development of a dechlorinating agent for dechlorination of reforming hydrogen with high chlorine capacity, high crushing strength, high wear resistance and long service life has very important practical significance and industrial application value for the petroleum refining industry. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a high chlorine capacity and long-life dechlorinating agent for dechlorination of reforming hydrogen and a preparation method thereof, so as to achieve the following invention objectives: to prepare a dechlorinating agent for dechlorination of reforming hydrogen with high chlorine capacity, high crushing strength, high wear resistance and long life.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A high chlorine capacity and long life dechlorinating agent for dechlorination of reformed hydrogen and a preparation method thereof, wherein the high chlorine capacity and long life dechlorinating agent for dechlorination of reformed hydrogen has an inorganic chlorine penetration capacity of 35.8-40.3% and a crushing strength of 174-180 N·cm -1 , the wear rate is 0.7~1.1%; The preparation method of the high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen comprises six steps of preparing a pre-impregnation liquid of nanocellulose loaded with an active promoter, preparing an ultrafine crystallized molecular sieve, preparing modified starch, preparing a slurry, extruding, and curing and calcining; The following are further improvements to the above technical solution: Step 1: Prepare a pre-impregnation solution of nanocellulose loaded with active promoter The nanocellulose and N,N-dimethylformamide are added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion rate is reduced to a low rate, and thionyl chloride is added, and the reaction is closed. After the reaction is continued until the temperature in the kettle is constant, a diamine substance is added, and the dispersion reaction is continued until no precipitation is precipitated, and then the dispersion stirring is stopped, and the separated solid is centrifuged, and the separated solid is washed with deionized water until the eluate is neutral, and then low-temperature drying is performed to obtain modified nanocellulose, and then the aqueous solution of modified nanocellulose and an active promoter is added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion is stopped, and the pre-impregnation solution of the nanocellulose loaded with the active promoter is obtained; The nanocellulose has a diameter of 4-12 nm and a length of 100-600 nm; The diamine substance is one of ethylenediamine, 1,6-hexanediamine, p-phenylenediamine, dimethylethylenediamine, diethylpropylenediamine, and 4-methylpentane-1,2-diamine; The active promoter is a mixture of copper salt and nickel salt; The copper salt is one of copper sulfate, copper nitrate and copper chloride; The nickel salt is one of nickel sulfate, nickel nitrate and nickel chloride; The mass ratio of the copper salt to the nickel salt is 3-9:7; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 10-30wt%; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 20-60:150-390:4-11:10-25; The modified nanocellulose and the active promoter aqueous solution have a mass ratio of 7 to 23:80; The high-speed shear dispersion has a dispersion rate of 8000-11000 rpm; The low dispersion rate is 3000-5000 rpm; The low temperature drying is performed at a temperature of 60 to 80° C. and a drying time of 9 to 16 hours.
[0008] Step 2: Preparation of ultrafine crystallized molecular sieve Add silicon source, aluminum source, sodium hydroxide, composite template agent and deionized water into a reaction kettle, stir and dissolve into a uniform solution, then add a complexing agent, stir into a colloidal state, stand and age to obtain a gel, then transfer the gel into a high-pressure reaction kettle, seal and crystallize at a constant temperature, then filter, wash with deionized water, and dry at a constant temperature to obtain an ultrafine crystallized molecular sieve; The silicon source is one of sodium metasilicate, diatomaceous earth and fumed silica; The aluminum source is one of sodium aluminate, pseudo-boehmite, and aluminum isopropoxide; The composite template agent is a mixture of Span and dihydroxyethyl alkyl betaine; The Span is one of Span 20 and Span 80; The dihydroxyethyl alkyl betaine is one of dodecyl dihydroxyethyl betaine and octadecyl dihydroxyethyl betaine; In the composite template, the mass ratio of Span and dihydroxyethyl alkyl betaine is 1-10:43; The complexing agent is one of lysine, 2-hydroxyphosphonoacetic acid, and ethylenediaminetetramethylenephosphonic acid; The mass ratio of the silicon source, aluminum source, sodium hydroxide, composite template, deionized water and complexing agent is 25-70:20-90:10-35:2-6:120-360:1.5-6; The static aging process lasts for 20 to 45 hours; The temperature of the closed constant temperature crystallization is 100-140°C, and the crystallization time is 5-9 hours; The deionized water washing is performed by washing with deionized water until the pH value of the washing solution is 9.5-10; The constant temperature drying has a drying temperature of 110-140° C. and a drying time of 6-14 hours.
[0009] Step 3: Preparation of modified starch Add amylose to a dilute sulfuric acid aqueous solution, stir and dissolve at a constant temperature, then add Span 85, stir and react at a constant temperature for 9 to 15 hours, cool to room temperature, add anhydrous ethanol, filter, wash the filtered solid with deionized water, precipitate with anhydrous ethanol, filter, and dry at low temperature to obtain modified starch; The number average molecular weight of the amylose is 30000-80000 g / mol; The mass fraction of sulfuric acid in the dilute sulfuric acid aqueous solution is 0.2-0.5wt%; The mass ratio of the amylose, the dilute sulfuric acid aqueous solution, and Span 85 is 10-45:100-360:5-20; The constant temperature is fully stirred, the constant temperature is 40-70°C, the stirring rate is 300-700 rpm, and the stirring time is 0.5-1.2 hours; The constant temperature stirring esterification reaction has a constant temperature of 95-100° C. and a stirring rate of 300-900 rpm; The deionized water washing is performed until the pH value of the washing solution is 6.5-7; The low-temperature drying has a drying temperature of 45-55° C. and a drying time of 15-23 hours.
[0010] Step 4: Prepare slurry Add the pre-impregnation liquid of nanocellulose loaded with active promoter, ultrafine crystallized molecular sieve, zinc oxide powder and deionized water into a double planetary mixer, stir and disperse completely, then add modified starch, pseudo-boehmite and sodium bentonite, stir vigorously and disperse evenly to obtain a slurry; The particle size of the zinc oxide powder is 40-100 nm; The pore volume of the pseudo-boehmite is 0.4-1.1 mL / g, and the specific surface area is 220-310 m 2 / g; The sodium bentonite has a blue absorption of 26-49 g / 100 g, a water absorption multiple of 15-30 times, a swelling capacity of 65-93 mL / 15 g, a colloid value of 540-800 mL / 15 g, and a particle size of 400-1000 meshes; The mass ratio of the nanocellulose loaded active promoter pre-impregnation liquid, ultrafine crystallized molecular sieve, zinc oxide powder, deionized water, modified starch, pseudo-boehmite, and sodium bentonite is 20-50:15-35:5-15:30-85:5-15:2-10:3-14; The stirring and dispersing process has a stirring rate of 70 to 110 rpm and a dispersing rate of 6000 to 9000 rpm; The strong stirring and dispersing has a stirring rate of 120-160 rpm and a dispersing rate of 10,000-13,000 rpm.
[0011] Step 5: Extrusion The slurry is injected into a twin-screw extruder, and the screw speed and the diameter of the die mouth are adjusted to extrude long strip particles. The cross-sectional diameter of the particles is controlled to be 2-5 mm and the length is 7-18 mm to obtain the original particles of the dechlorinating agent.
[0012] Step 6: Curing and calcining The original particles of the dechlorinating agent are dried, aged at room temperature, cured at a constant temperature and calcined to obtain a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen; The drying temperature is 45-60°C and the drying time is 20-36 hours; The room temperature aging, the relative air humidity of the aging environment is 30-50%, and the aging time is 20-30 hours; The constant temperature curing, the dechlorination agent original particles after room temperature aging are placed in a muffle furnace, and the temperature is raised from room temperature to 110-160° C. at a heating rate of 1-2.5° C. / min, and the constant temperature curing is performed for 8-13 hours; The calcination is carried out by heating the temperature from the constant temperature curing temperature to 450-630° C. at a heating rate of 1-3° C. / min, calcining at the constant temperature for 10-16 hours, and then naturally cooling the temperature to room temperature.
[0013] Compared with the prior art, the present invention achieves the following beneficial effects: 1. In order to introduce two active promoters, copper oxide and nickel oxide, into the dechlorinating agent to improve the dechlorination performance, the present invention specially designs a process for impregnating and adsorbing copper and nickel metal ions loaded on modified nanocellulose. The process is specifically as follows: first, the nanocellulose is uniformly dispersed in N,N-dimethylformamide, and then thionyl chloride is added. Under the solvation and catalytic action of N,N-dimethylformamide, thionyl chloride rapidly reacts with the active hydroxyl and carboxyl groups on the nanocellulose to undergo acyl chloride reaction, and the generated acyl chloride bond reacts with the subsequently added diamine substance to form an amide structure. Because diamine substances are added, the terminal of the amide structure formed by the above reaction is still an amino group, and this terminal amino group has a strong adsorption effect on copper and nickel metal ions. Therefore, a large amount of copper and nickel metal ions are adsorbed on the surface of the modified nanofibers. In the subsequent slurry preparation process, the copper and nickel metal ions will be uniformly dispersed in the slurry along with the modified nanofibers. And achieve very uniform dispersion, then in the slurry extrusion process and the subsequent curing and roasting process, the copper and nickel metal ions will maintain a uniform and stable dispersion state inside the dechlorinating agent, and finally after roasting and oxidation, evenly distributed copper oxide and nickel oxide will be formed inside the finished dechlorinating agent. These two oxides form particles with very fine particle sizes due to their uniform dispersion. Such oxide particles have a very large specific surface area, which will greatly promote the dechlorination performance of the dechlorinating agent and improve the penetration capacity of inorganic chlorine in the dechlorinating agent. In addition, this oxide with excellent dispersion has little effect on the dense sintering of the dechlorinating agent, and in the process of oxide formation, nanocellulose will be ablated to form micro-mesoporous channels. The size of these channels is very small, which can ensure that the mechanical properties of the dechlorinating agent are not greatly affected. Secondly, these micro-mesoporous channels provide convenient conditions for the contact between hydrogen chloride and copper oxide and nickel oxide, so that the dechlorination performance of the dechlorinating agent is effectively and significantly improved. 2. The present invention successfully prepares ultrafine crystallized molecular sieves by using a composite template composed of Span and dihydroxyethyl alkyl betaine and complexing agents such as lysine, 2-hydroxyphosphonoacetic acid, and ethylenediaminetetramethylenephosphonic acid. The ultrafine crystallization of the molecular sieve can increase the specific surface area inside the molecular sieve, thereby greatly improving the dechlorination performance of the molecular sieve, and further improves the crushing resistance and wear resistance of the molecular sieve, and ultimately promotes the relevant mechanical properties and service life of the dechlorination agent particles; 3. In the present invention, under the catalytic action of dilute sulfuric acid, Span 85 is used to react with amylose to undergo an esterification reaction, thereby effectively modifying the starch. After the amylose is esterified with Span 85, its cold water solubility is greatly improved. Since Span 85 is a nonionic surfactant, the starch structure after esterification also has some properties of a nonionic surfactant. In the present invention, the specific functions of the slurry preparation process and the extrusion process are to thicken and increase the viscosity of the slurry, improve the surface smoothness of the slurry during extrusion, and well disperse and densely wrap the ultrafine crystallized molecular sieve, zinc oxide powder, pseudo-boehmite, sodium bentonite and other particles. The above functions of the modified starch can promote the uniform bonding of the components inside the dechlorinating agent and the close contact between the particles, thereby promoting the effective sintering between the particles during the roasting process, and finally enhancing the density of the dechlorinating agent during the overall sintering process, thereby improving the crushing strength and wear resistance of the dechlorinating agent; 4. The high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen obtained by the present invention has an inorganic chlorine penetration capacity of 35.8-40.3% and a crushing strength of 174-180 N·cm -1 The wear rate is 0.7~1.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a scanning electron microscope photograph of the cross-section of the high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen obtained in Example 1, magnified 50,000 times. DETAILED DESCRIPTION
[0015] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0016] Example 1: A method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen Step 1: Prepare a pre-impregnation solution of nanocellulose loaded with active promoter The nanocellulose and N,N-dimethylformamide are added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion rate is reduced to a low rate, and thionyl chloride is added, and the reaction is closed. After the reaction is continued until the temperature in the kettle is constant, a diamine substance is added, and the dispersion reaction is continued until no precipitation is precipitated, and then the dispersion stirring is stopped, and the separated solid is centrifuged, and the separated solid is washed with deionized water until the eluate is neutral, and then low-temperature drying is performed to obtain modified nanocellulose, and then the aqueous solution of modified nanocellulose and an active promoter is added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion is stopped, and the pre-impregnation solution of the nanocellulose loaded with the active promoter is obtained; The nanocellulose has a diameter of 10 nm and a length of 400 nm; The diamine substance is ethylenediamine; The active promoter is a mixture of copper salt and nickel salt; The copper salt is copper sulfate; The nickel salt is nickel sulfate; The mass ratio of the copper salt to the nickel salt is 5:7; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 22wt%; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 45:330:7:18; The modified nanocellulose and the active promoter aqueous solution have a mass ratio of 13:80; The high-speed shear dispersion has a dispersion rate of 9000 rpm; The low dispersion rate is 4800 rpm; The low-temperature drying is performed at a temperature of 75° C. and a drying time of 11 hours.
[0017] Step 2: Preparation of ultrafine crystallized molecular sieve Add silicon source, aluminum source, sodium hydroxide, composite template agent and deionized water into a reaction kettle, stir and dissolve into a uniform solution, then add a complexing agent, stir into a colloidal state, stand and age to obtain a gel, then transfer the gel into a high-pressure reaction kettle, seal and crystallize at a constant temperature, then filter, wash with deionized water, and dry at a constant temperature to obtain an ultrafine crystallized molecular sieve; The silicon source is sodium metasilicate; The aluminum source is sodium metaaluminate; The composite template agent is a mixture of Span and dihydroxyethyl alkyl betaine; The Span is Span 20; The dihydroxyethyl alkyl betaine is dodecyl dihydroxyethyl betaine; In the composite template, the mass ratio of Span and dihydroxyethyl alkyl betaine is 8:43; The complexing agent is lysine; The mass ratio of the silicon source, aluminum source, sodium hydroxide, composite template, deionized water and complexing agent is 44:60:20:5:220:4; The static aging time is 35 hours; The temperature of the closed constant temperature crystallization is 130°C and the crystallization time is 8 hours; The deionized water washing is performed by washing with deionized water until the pH value of the washing solution is 9.8; The constant temperature drying has a drying temperature of 120° C. and a drying time of 11 hours.
[0018] Step 3: Preparation of modified starch Add amylose to a dilute sulfuric acid aqueous solution, stir and dissolve at a constant temperature, then add Span 85, stir and react at a constant temperature for 12 hours, cool to room temperature, add anhydrous ethanol, filter, wash the filtered solid with deionized water, precipitate with anhydrous ethanol, filter, and dry at low temperature to obtain modified starch; The number average molecular weight of the amylose is 60000 g / mol; The mass fraction of sulfuric acid in the dilute sulfuric acid aqueous solution is 0.4wt%; The mass ratio of the amylose, the dilute sulfuric acid aqueous solution, and Span 85 is 30:200:13; The constant temperature was 60°C, the stirring rate was 600 rpm, and the stirring time was 1 hour. The constant temperature stirring esterification reaction has a constant temperature of 98° C. and a stirring rate of 700 rpm; The deionized water washing is performed until the pH value of the washing solution is 6.7; The low-temperature drying has a drying temperature of 53° C. and a drying time of 20 hours.
[0019] Step 4: Prepare slurry Add the pre-impregnation liquid of nanocellulose loaded with active promoter, ultrafine crystallized molecular sieve, zinc oxide powder and deionized water into a double planetary mixer, stir and disperse completely, then add modified starch, pseudo-boehmite and sodium bentonite, stir vigorously and disperse evenly to obtain a slurry; The particle size of the zinc oxide powder is 60 nm; The pore volume of the pseudo-boehmite is 0.8 mL / g and the specific surface area is 270 m 2 / g; The sodium bentonite has a blue absorption capacity of 29g / 100g, a water absorption multiple of 20 times, a swelling capacity of 83mL / 15g, a colloid value of 640mL / 15g, and a particle size of 800 mesh; The mass ratio of the nanocellulose-loaded active promoter pre-impregnation liquid, ultrafine crystallized molecular sieve, zinc oxide powder, deionized water, modified starch, pseudo-boehmite, and sodium bentonite is 35:20:11:60:9:8:11; The stirring and dispersing process has a stirring rate of 90 rpm and a dispersing rate of 8000 rpm; The strong stirring and dispersing has a stirring rate of 150 rpm and a dispersing rate of 11000 rpm.
[0020] Step 5: Extrusion The slurry was injected into a twin-screw extruder, and the screw speed and the diameter of the die opening were adjusted to extrude long strip particles. The cross-sectional diameter of the particles was controlled to be 3 mm and the length to be 13 mm, thereby obtaining the original particles of the dechlorinating agent.
[0021] Step 6: Curing and calcining The original particles of the dechlorinating agent are dried, aged at room temperature, cured at a constant temperature and calcined to obtain a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen; The drying temperature is 50°C and the drying time is 28 hours; The room temperature aging, the relative air humidity of the aging environment is 39%, and the aging time is 27 hours; The constant temperature curing, the dechlorination agent original particles after room temperature aging are placed in a muffle furnace, and the temperature is raised from room temperature to 140°C at a heating rate of 2°C / min, and the constant temperature curing is performed for 10 hours; The calcination was carried out by heating the temperature from the constant temperature curing temperature to 550° C. at a heating rate of 2° C. / min, calcining at the constant temperature for 14 hours, and then naturally cooling the temperature to room temperature.
[0022] Example 2: A method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen Step 1: Prepare a pre-impregnation solution of nanocellulose loaded with active promoter The nanocellulose and N,N-dimethylformamide are added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion rate is reduced to a low rate, and thionyl chloride is added, and the reaction is closed. After the reaction is continued until the temperature in the kettle is constant, a diamine substance is added, and the dispersion reaction is continued until no precipitation is precipitated, and then the dispersion stirring is stopped, and the separated solid is centrifuged, and the separated solid is washed with deionized water until the eluate is neutral, and then low-temperature drying is performed to obtain modified nanocellulose, and then the aqueous solution of modified nanocellulose and an active promoter is added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion is stopped, and the pre-impregnation solution of the nanocellulose loaded with the active promoter is obtained; The nanocellulose has a diameter of 4 nm and a length of 100 nm; The diamine substance is 1,6-hexanediamine; The active promoter is a mixture of copper salt and nickel salt; The copper salt is copper nitrate; The nickel salt is nickel nitrate; The mass ratio of the copper salt to the nickel salt is 3:7; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 10wt%; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 20:150:4:10; The modified nanocellulose and the active promoter aqueous solution have a mass ratio of 7:80; The high-speed shear dispersion has a dispersion rate of 8000 rpm; The low dispersion rate is 3000 rpm; The low temperature drying is performed at a temperature of 60° C. and a drying time of 9 hours.
[0023] Step 2: Preparation of ultrafine crystallized molecular sieve Add silicon source, aluminum source, sodium hydroxide, composite template agent and deionized water into a reaction kettle, stir and dissolve into a uniform solution, then add a complexing agent, stir into a colloidal state, stand and age to obtain a gel, then transfer the gel into a high-pressure reaction kettle, seal and crystallize at a constant temperature, then filter, wash with deionized water, and dry at a constant temperature to obtain an ultrafine crystallized molecular sieve; The silicon source is diatomaceous earth; The aluminum source is pseudo-boehmite; The composite template agent is a mixture of Span and dihydroxyethyl alkyl betaine; The Span is Span 80; The dihydroxyethyl alkyl betaine is octadecyl dihydroxyethyl betaine; In the composite template, the mass ratio of Span and dihydroxyethyl alkyl betaine is 1:43; The complexing agent is 2-hydroxyphosphonoacetic acid; The mass ratio of the silicon source, aluminum source, sodium hydroxide, composite template, deionized water and complexing agent is 25:20:10:2:120:1.5; The static aging time is 20 hours; The temperature of the closed constant temperature crystallization is 100°C and the crystallization time is 5 hours; The deionized water washing is performed by washing with deionized water until the pH value of the washing solution is 9.5; The constant temperature drying has a drying temperature of 110° C. and a drying time of 6 hours.
[0024] Step 3: Preparation of modified starch Add amylose to a dilute sulfuric acid aqueous solution, stir and dissolve at a constant temperature, then add Span 85, stir and react at a constant temperature for 9 hours, cool to room temperature, add anhydrous ethanol, filter, wash the filtered solid with deionized water, precipitate with anhydrous ethanol, filter, and dry at low temperature to obtain modified starch; The number average molecular weight of the amylose is 30000 g / mol; The mass fraction of sulfuric acid in the dilute sulfuric acid aqueous solution is 0.2wt%; The mass ratio of the amylose, the dilute sulfuric acid aqueous solution, and Span 85 is 10:100:5; The constant temperature was fully stirred, the constant temperature was 40°C, the stirring rate was 300 rpm, and the stirring time was 0.5 hours; The constant temperature stirring esterification reaction has a constant temperature of 95° C. and a stirring rate of 300 rpm; The deionized water washing is performed until the pH value of the washing solution is 6.5; The low-temperature drying has a drying temperature of 45° C. and a drying time of 15 hours.
[0025] Step 4: Prepare slurry Add the pre-impregnation liquid of nanocellulose loaded with active promoter, ultrafine crystallized molecular sieve, zinc oxide powder and deionized water into a double planetary mixer, stir and disperse completely, then add modified starch, pseudo-boehmite and sodium bentonite, stir vigorously and disperse evenly to obtain a slurry; The particle size of the zinc oxide powder is 40 nm; The pore volume of the pseudo-boehmite is 0.4 mL / g and the specific surface area is 220 m 2 / g; The sodium bentonite has a blue absorption capacity of 26 g / 100 g, a water absorption multiple of 15 times, a swelling capacity of 65 mL / 15 g, a colloid value of 540 mL / 15 g, and a particle size of 400 meshes; The mass ratio of the nanocellulose-loaded active promoter pre-impregnation liquid, ultrafine crystallized molecular sieve, zinc oxide powder, deionized water, modified starch, pseudo-boehmite, and sodium bentonite is 20:15:5:30:5:2:3; The stirring and dispersing process has a stirring rate of 70 rpm and a dispersing rate of 6000 rpm; The strong stirring and dispersing has a stirring rate of 120 rpm and a dispersing rate of 10,000 rpm.
[0026] Step 5: Extrusion The slurry was injected into a twin-screw extruder, and the screw speed and the diameter of the die opening were adjusted to extrude long strip particles. The cross-sectional diameter of the particles was controlled to be 2 mm and the length to be 7 mm, thereby obtaining the original particles of the dechlorinating agent.
[0027] Step 6: Curing and calcining The original particles of the dechlorinating agent are dried, aged at room temperature, cured at a constant temperature and calcined to obtain a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen; The drying temperature is 45°C and the drying time is 20 hours; The room temperature aging, the relative air humidity of the aging environment is 30%, and the aging time is 20 hours; The constant temperature curing, the dechlorination agent original particles after room temperature aging are placed in a muffle furnace, and the temperature is raised from room temperature to 110°C at a heating rate of 1°C / min, and the constant temperature curing is performed for 8 hours; The calcination was carried out by heating the temperature from the constant temperature curing temperature to 450° C. at a heating rate of 1° C. / min, calcining at the constant temperature for 10 hours, and then naturally cooling the temperature to room temperature.
[0028] Example 3: A method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen Step 1: Prepare a pre-impregnation solution of nanocellulose loaded with active promoter The nanocellulose and N,N-dimethylformamide are added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion rate is reduced to a low rate, and thionyl chloride is added, and the reaction is closed. After the reaction is continued until the temperature in the kettle is constant, a diamine substance is added, and the dispersion reaction is continued until no precipitation is precipitated, and then the dispersion stirring is stopped, and the separated solid is centrifuged, and the separated solid is washed with deionized water until the eluate is neutral, and then low-temperature drying is performed to obtain modified nanocellulose, and then the aqueous solution of modified nanocellulose and an active promoter is added to a high-speed dispersion kettle, and dispersed by high-speed shearing until the solution is translucent, and then the dispersion is stopped, and the pre-impregnation solution of the nanocellulose loaded with the active promoter is obtained; The nanocellulose has a diameter of 12 nm and a length of 600 nm; The diamine substance is p-phenylenediamine; The active promoter is a mixture of copper salt and nickel salt; The copper salt is copper chloride; The nickel salt is nickel chloride; The mass ratio of the copper salt to the nickel salt is 9:7; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 30wt%; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 60:390:11:25; The modified nanocellulose and the active promoter aqueous solution have a mass ratio of 23:80; The high-speed shear dispersion has a dispersion rate of 11,000 rpm; The low dispersion rate is 5000 rpm; The low-temperature drying is performed at a temperature of 80° C. and a drying time of 16 hours.
[0029] Step 2: Preparation of ultrafine crystallized molecular sieve Add silicon source, aluminum source, sodium hydroxide, composite template agent and deionized water into a reaction kettle, stir and dissolve into a uniform solution, then add a complexing agent, stir into a colloidal state, stand and age to obtain a gel, then transfer the gel into a high-pressure reaction kettle, seal and crystallize at a constant temperature, then filter, wash with deionized water, and dry at a constant temperature to obtain an ultrafine crystallized molecular sieve; The silicon source is fumed silicon dioxide; The aluminum source is aluminum isopropoxide; The composite template agent is a mixture of Span and dihydroxyethyl alkyl betaine; The Span is Span 20; The dihydroxyethyl alkyl betaine is dodecyl dihydroxyethyl betaine; In the composite template, the mass ratio of Span and dihydroxyethyl alkyl betaine is 10:43; The complexing agent is ethylenediaminetetramethylenephosphonic acid; The mass ratio of the silicon source, aluminum source, sodium hydroxide, composite template, deionized water and complexing agent is 70:90:35:6:360:6; The static aging time is 45 hours; The temperature of the closed constant temperature crystallization is 140°C and the crystallization time is 9 hours; The deionized water washing is performed by washing with deionized water until the pH value of the washing solution is 10; The constant temperature drying has a drying temperature of 140° C. and a drying time of 14 hours.
[0030] Step 3: Preparation of modified starch Add amylose to a dilute sulfuric acid aqueous solution, stir and dissolve at a constant temperature, then add Span 85, stir and react at a constant temperature for 15 hours, cool to room temperature, add anhydrous ethanol, filter, wash the filtered solid with deionized water, precipitate with anhydrous ethanol, filter, and dry at low temperature to obtain modified starch; The number average molecular weight of the amylose is 80000 g / mol; The mass fraction of sulfuric acid in the dilute sulfuric acid aqueous solution is 0.5wt%; The mass ratio of the amylose, the dilute sulfuric acid aqueous solution, and Span 85 is 45:360:20; The constant temperature was fully stirred, the constant temperature was 70°C, the stirring rate was 700 rpm, and the stirring time was 1.2 hours; The constant temperature stirring esterification reaction has a constant temperature of 100° C. and a stirring rate of 900 rpm; The deionized water washing is performed until the pH value of the washing solution is 7; The low-temperature drying has a drying temperature of 55° C. and a drying time of 23 hours.
[0031] Step 4: Prepare slurry Add the pre-impregnation liquid of nanocellulose loaded with active promoter, ultrafine crystallized molecular sieve, zinc oxide powder and deionized water into a double planetary mixer, stir and disperse completely, then add modified starch, pseudo-boehmite and sodium bentonite, stir vigorously and disperse evenly to obtain a slurry; The particle size of the zinc oxide powder is 100 nm; The pore volume of the pseudo-boehmite is 1.1 mL / g and the specific surface area is 310 m 2 / g; The sodium bentonite has a blue absorption capacity of 49 g / 100 g, a water absorption multiple of 30 times, a swelling capacity of 93 mL / 15 g, a colloid value of 800 mL / 15 g, and a particle size of 1000 mesh; The mass ratio of the nanocellulose loaded active promoter pre-impregnation liquid, ultrafine crystallized molecular sieve, zinc oxide powder, deionized water, modified starch, pseudo-boehmite, and sodium bentonite is 50: 35:15:85:15:10:14; The stirring and dispersing process has a stirring rate of 110 rpm and a dispersing rate of 9000 rpm; The strong stirring and dispersing has a stirring rate of 160 rpm and a dispersing rate of 13,000 rpm.
[0032] Step 5: Extrusion The slurry was injected into a twin-screw extruder, and the screw speed and the diameter of the die opening were adjusted to extrude long strip particles. The cross-sectional diameter of the particles was controlled to be 5 mm and the length to be 18 mm, thereby obtaining the original particles of the dechlorinating agent.
[0033] Step 6: Curing and calcining The original particles of the dechlorinating agent are dried, aged at room temperature, cured at a constant temperature and calcined to obtain a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen; The drying temperature is 60°C and the drying time is 36 hours; The room temperature aging, the relative air humidity of the aging environment is 50%, and the aging time is 30 hours; The constant temperature curing, the dechlorination agent original particles after room temperature aging are placed in a muffle furnace, and the temperature is raised from room temperature to 160°C at a heating rate of 2.5°C / min, and the constant temperature curing is performed for 13 hours; The calcination was carried out by heating the temperature from the constant temperature curing temperature to 630° C. at a heating rate of 3° C. / min, calcining at the constant temperature for 16 hours, and then naturally cooling the temperature to room temperature.
[0034] Comparative Example 1: Based on Example 1, in step 1, in preparing a pre-impregnation solution of nanocellulose loaded with an active promoter, modified nanocellulose is not prepared, and the active promoter is directly loaded with nanocellulose to prepare a pre-impregnation solution. The specific operation is as follows: Step 1: Prepare a pre-impregnation solution of nanocellulose loaded with active promoter The aqueous solution of nanocellulose and the active promoter is added into a high-speed dispersing kettle, and after high-speed shearing dispersion until the solution becomes translucent, the dispersion is stopped, and the solution is allowed to stand for immersion and adsorption for 35 hours to obtain a pre-impregnation solution of nanocellulose loaded with the active promoter; The cross-sectional diameter of the nanocellulose is 10 nm and the length is 400 nm; The active promoter is a mixture of copper salt and nickel salt; The copper salt is copper sulfate; The nickel salt is nickel sulfate; The mass ratio of the copper salt to the nickel salt is 5:7; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 22wt%; The modified nanocellulose and the active promoter aqueous solution have a mass ratio of 13:80; The high-speed shear dispersion has a dispersion rate of 9000 rpm; The operations of steps 2, 3, 4, 5 and 6 are the same as those of Example 1.
[0035] Comparative Example 2: On the basis of Example 1, in step 1, in preparing the pre-impregnation liquid of nanocellulose loaded with an active promoter, the modified nanocellulose is not loaded with an active promoter, and the modified nanocellulose is directly used to prepare a pre-dispersion liquid, that is, step 1 is modified to prepare a modified nanocellulose pre-dispersion liquid, and in step 4, in preparing the slurry, 35 parts of the pre-impregnation liquid of nanocellulose loaded with an active promoter are replaced with 35 parts of the modified nanocellulose pre-dispersion liquid in an equal amount, and the specific operation is as follows: Step 1: Preparation of modified nanocellulose pre-dispersion Add nanocellulose and N,N-dimethylformamide to a high-speed dispersing kettle, disperse at high speed until the solution is translucent, reduce the dispersion rate to a low level, add thionyl chloride, react in a closed manner, react until the temperature in the kettle remains constant, then add a diamine substance, continue the dispersion reaction until no precipitation is precipitated, stop dispersing and stirring, centrifuge, wash the separated solid with deionized water until the eluate is neutral, dry at low temperature to obtain modified nanocellulose, then add the modified nanocellulose and deionized water to a high-speed dispersing kettle, disperse at high speed until the solution is translucent, stop dispersing, and obtain a modified nanocellulose pre-dispersion liquid; The cross-sectional diameter of the nanocellulose is 10 nm and the length is 400 nm; The diamine substance is ethylenediamine; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 45:330:7:18; The mass ratio of the modified nanocellulose and deionized water is 13:80; The high-speed shear dispersion has a dispersion rate of 9000 rpm; The low dispersion rate is 4800 rpm; The low temperature drying is performed at a temperature of 75°C and a drying time of 11 hours; The operations of steps 2 and 3 are the same as those of Example 1; Step 4: Prepare slurry The 35 parts of nanocellulose loaded active promoter pre-impregnation solution were replaced by 35 parts of modified nanocellulose pre-dispersion solution, and the other operations were the same as in Example 1; The operations of steps 5 and 6 are the same as those of Example 1.
[0036] Comparative Example 3: Based on Example 1, in step 2, in the preparation of ultrafine crystallized molecular sieve, no composite template agent is added, and 5 parts of the composite template agent are replaced by 5 parts of deionized water in equal amounts. The specific operation is as follows: The operation of step 1 is the same as that of embodiment 1; Step 2: Preparation of ultrafine crystallized molecular sieve 5 parts of the composite template agent were replaced by 5 parts of deionized water, and the other operations were the same as in Example 1; The operations of steps 3, 4, 5 and 6 are the same as those of Example 1.
[0037] Comparative Example 4: Based on Example 1, in step 2, in the preparation of ultrafine crystallized molecular sieve, no complexing agent is added, and 4 parts of complexing agent are replaced by 4 parts of deionized water in equal amounts. The specific operation is as follows: The operation of step 1 is the same as that of embodiment 1; Step 2: Preparation of ultrafine crystallized molecular sieve The 4 parts of complexing agent were replaced by 4 parts of deionized water, and the other operations were the same as in Example 1; The operations of steps 3, 4, 5 and 6 are the same as those of Example 1.
[0038] Comparative Example 5: Based on Example 1, step 3, preparing modified starch, is not performed. In step 4, in preparing the slurry, 9 parts of modified starch are replaced by 9 parts of amylose. The specific operation is as follows: The operations of steps 1 and 2 are the same as those of Example 1; Without performing step 3, preparing modified starch; Step 4: Prepare slurry 9 parts of modified starch were replaced by 9 parts of amylose, and other operations were the same as in Example 1; The number average molecular weight of the amylose is 60000 g / mol; The operations of steps 5 and 6 are the same as those of Example 1.
[0039] Performance Testing: The high chlorine capacity and long life dechlorinating agent for dechlorination of reformed hydrogen obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5 was tested for the following indicators: 1. The test method for inorganic chlorine penetration is as follows: reformed hydrogen with a hydrogen chloride content of about 5μL / L is heated at 25°C, 2.5MPa, and a hydrogen space velocity of 2500h -1 Under the conditions of , the dechlorinating agent is loaded to carry out the reformed hydrogen dechlorination experiment, and the chlorine content in the reformed hydrogen flowing out of the dechlorination tank is measured. When the chlorine content of the effluent is greater than 0.5μL / L, it can be regarded as breakthrough. According to the formula: breakthrough chlorine capacity = (mass content of chlorine in the dechlorinating agent after breakthrough) / (total mass of the dechlorinating agent after breakthrough) × 100%, the breakthrough chlorine capacity of the dechlorinating agent is obtained; 2. Crushing strength: refer to "HG / T 2782-2011 Determination of crushing resistance of fertilizer catalyst particles" to test the crushing strength; 3. Wear rate: refer to "HG / T 2976-2011 Determination of Wear Rate of Fertilizer Catalysts" to test the wear rate; The specific test results are shown in Table 1: Table 1
[0040] From the test data in Table 1, it can be seen that the inorganic chlorine penetration capacity of Examples 1-3 is above 35%, and the crushing strength is greater than 170N·cm -1, the abrasion rate is less than 1.1%, which shows that the dechlorinating agent for reforming hydrogen dechlorination obtained by the present invention has a very high inorganic chlorine penetration chlorine capacity, and also has performance advantages such as high crushing strength and low abrasion rate, which is very critical to improving the service life of the dechlorinating agent. Therefore, the dechlorinating agent obtained by the present invention has significant advantages such as high chlorine capacity, high mechanical strength and long service life; in Comparative Example 1, the pre-impregnation liquid of nanocellulose loaded with active promoter is not prepared, and the active promoter is directly loaded with nanocellulose. The inorganic chlorine penetration chlorine capacity of the comparative example is reduced to 19.1%, and the crushing strength and abrasion rate are not significantly changed compared with Example 1. This shows that if nanocellulose is not modified, it is difficult to effectively load the active promoter with excellent dechlorination performance, which leads to The penetration chlorine capacity of comparative example 1 is greatly reduced, on the other hand, it also shows that the modification of nanocellulose has little effect on the mechanical properties of the dechlorinating agent; in comparative example 2, the modified nanocellulose is not loaded with an active promoter, and the penetration chlorine capacity of inorganic chlorine in comparative example 2 is reduced to 17.5%, and the crushing strength and abrasion rate have no obvious changes, which shows that the loaded active promoter, that is, nickel-copper oxide, can greatly improve the dechlorination ability of the dechlorinating agent, and these two metal oxides can be tightly sintered into a whole with other raw materials of the dechlorinating agent, and have little effect on the mechanical properties of the dechlorinating agent particles; in comparative example 3, no composite template is added during the preparation of the ultrafine crystallized molecular sieve, and the penetration chlorine capacity of inorganic chlorine in comparative example 3 is reduced to 11.9%, and the crushing strength is reduced to 105 N·cm -1 , the wear rate also increased to 3.7%, which shows that it is difficult to obtain an ultrafine crystallized molecular sieve without adding a composite template agent. The molecular sieve with poor crystal fineness has poor dechlorination performance, which leads to a significant decrease in the overall penetration chlorine capacity of the dechlorinating agent. Moreover, the molecular sieve itself has too coarse grains, and its mechanical properties will also be greatly reduced, which in turn causes a significant decrease in the overall mechanical properties of the dechlorinating agent particles. In Comparative Example 4, no complexing agent was added during the preparation of the ultrafine crystallized molecular sieve. Similar to Comparative Example 3, the penetration chlorine capacity of Comparative Example 4 dropped to 10.3%, and the crushing strength and wear resistance both dropped sharply. This shows that the addition of a complexing agent can It can effectively improve the refinement of the molecular sieve, and then improve the dechlorination performance and mechanical properties of the molecular sieve, and finally promote the overall dechlorination performance as well as the crushing resistance and wear resistance of the dechlorinator; in Comparative Example 5, no modified starch was added, and amylose was directly added. The penetration chlorine capacity of Comparative Example 5 was significantly reduced to 19.5%, and the crushing strength and wear resistance were also greatly reduced. This shows that the modified starch has a crucial influence on the effective bonding of the components in the molding process of the dechlorinator, the formation of micropores in the sintering process, and the sintering between the particles of the components in the sintering process, and finally affects the penetration chlorine capacity as well as the crushing resistance and wear resistance of the dechlorinator.
[0041] Attached Figure 1The high chlorine capacity and long life dechlorinating agent for dechlorination of reformed hydrogen obtained in Example 1 is a cross-section magnified 50,000 times. It can be seen from the electron microscope photograph that the molecular sieve and zinc oxide particles inside the dechlorinating agent are sintered together, and there are micron- to submicron-sized pores between the particles formed by the decomposition of nanocellulose and starch. This pore structure ensures the effective contact between the internal adsorbed active substances and the hydrogen chloride in the reformed hydrogen and can maintain the dechlorinating agent with very high crushing strength and wear resistance.
[0042] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen, characterized in that: The preparation method of the high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen comprises six steps of preparing a pre-impregnation liquid of nanocellulose loaded with an active promoter, preparing an ultrafine crystallized molecular sieve, preparing modified starch, preparing a slurry, extruding, and curing and calcining; The method for preparing a pre-impregnation liquid of nanocellulose loaded with an active promoter comprises adding nanocellulose and N,N-dimethylformamide into a high-speed dispersing kettle, dispersing until the solution is translucent, reducing the dispersing rate to a low level, adding thionyl chloride, reacting in a closed manner until the temperature in the kettle remains constant, adding a diamine substance, continuing the reaction until no precipitation is produced, stopping the dispersion, washing the solid separated by centrifugation with deionized water, and drying at low temperature to obtain modified nanocellulose, then adding an aqueous solution of the modified nanocellulose and the active promoter into a high-speed dispersing kettle, dispersing until the solution is translucent, stopping the dispersion, and allowing the pre-impregnation liquid of nanocellulose loaded with an active promoter to be obtained after standing, impregnating, and adsorbing; The method for preparing the ultrafine crystallized molecular sieve comprises adding a silicon source, an aluminum source, sodium hydroxide, a composite template agent, and deionized water into a reaction kettle, stirring and dissolving into a uniform solution, adding a complexing agent, stirring into a colloidal state, standing and aging to obtain a gel, and then performing closed constant temperature crystallization, filtering, washing with deionized water, and constant temperature drying to obtain the ultrafine crystallized molecular sieve; In the preparation of the modified starch, the amylose is added into a dilute sulfuric acid aqueous solution, and Span 85 is added after dissolving, and the mixture is stirred at a constant temperature until the esterification reaction is complete, and then the mixture is cooled to room temperature, anhydrous ethanol is added, and the mixture is filtered. The filtered solid is washed with deionized water, precipitated with anhydrous ethanol, filtered, and dried at low temperature to obtain the modified starch.
2. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 1, characterized in that: The nanocellulose has a diameter of 4-12 nm and a length of 100-600 nm; The diamine substance is one of ethylenediamine, 1,6-hexanediamine, p-phenylenediamine, dimethylethylenediamine, diethylpropylenediamine, and 4-methylpentane-1,2-diamine; The active promoter is a mixture of copper salt and nickel salt; The copper salt is one of copper sulfate, copper nitrate and copper chloride; The nickel salt is one of nickel sulfate, nickel nitrate and nickel chloride; The aqueous solution of the active promoter, wherein the mass fraction of the active promoter is 10-30wt%; The mass ratio of the nanocellulose, N,N-dimethylformamide, thionyl chloride and diamine substances is 20-60:150-390:4-11:10-25; The mass ratio of the modified nanocellulose and the aqueous solution of the active promoter is 7-23:
80.
3. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 1, characterized in that: The composite template agent is a mixture of Span and dihydroxyethyl alkyl betaine; The Span is one of Span 20 and Span 80; The dihydroxyethyl alkyl betaine is one of dodecyl dihydroxyethyl betaine and octadecyl dihydroxyethyl betaine; The complexing agent is one of lysine, 2-hydroxyphosphonoacetic acid, and ethylenediaminetetramethylenephosphonic acid; The silicon source is one of sodium metasilicate, diatomaceous earth and fumed silica; The aluminum source is one of sodium aluminate, pseudo-boehmite, and aluminum isopropoxide; The mass ratio of the silicon source, the aluminum source, the sodium hydroxide, the composite template agent, the deionized water and the complexing agent is 25-70:20-90:10-35:2-6:120-360:1.5-6.
4. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 1, characterized in that: The number average molecular weight of the amylose is 30000-80000 g / mol; The mass fraction of sulfuric acid in the dilute sulfuric acid aqueous solution is 0.2-0.5wt%; The mass ratio of the amylose, the dilute sulfuric acid aqueous solution and Span 85 is 10-45:100-360:5-20.
5. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 1, characterized in that: The slurry is prepared by adding the pre-impregnation liquid of the nanocellulose loaded active promoter, the ultrafine crystallized molecular sieve, the zinc oxide powder, and the deionized water into a double planetary mixer, stirring and dispersing them completely, and then adding the modified starch, pseudo-boehmite, and sodium bentonite, stirring and dispersing them vigorously to obtain the slurry; The particle size of the zinc oxide powder is 40-100 nm; The pore volume of the pseudo-boehmite is 0.4-1.1 mL / g, and the specific surface area is 220-310 m 2 / g; The sodium bentonite has a blue absorption of 26-49 g / 100 g, a water absorption multiple of 15-30 times, a swelling capacity of 65-93 mL / 15 g, a colloid value of 540-800 mL / 15 g, and a particle size of 400-1000 meshes; The mass ratio of the nanocellulose-loaded active promoter pre-impregnation liquid, ultrafine crystallized molecular sieve, zinc oxide powder, deionized water, modified starch, pseudo-boehmite and sodium bentonite is 20-50:15-35:5-15:30-85:5-15:2-10:3-14.
6. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 5, characterized in that: The extrusion is to inject the slurry into a twin-screw extruder, adjust the screw speed and the diameter of the die head, extrude long strip particles, control the cross-sectional diameter of the particles to be 2-5 mm, and the length to be 7-18 mm, to obtain the original particles of the dechlorinating agent.
7. The method for preparing a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen according to claim 6, characterized in that: The curing and roasting process is to dry the original particles of the dechlorinating agent, age them at room temperature, cure them at a constant temperature and roast them to obtain a high chlorine capacity and long life dechlorinating agent for dechlorination of reforming hydrogen.
8. A high chlorine capacity and long life dechlorinating agent for dechlorination of reformed hydrogen prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The high chlorine capacity and long life dechlorination agent for dechlorination of reforming hydrogen has an inorganic chlorine penetration capacity of 35.8-40.3% and a crushing strength of 174-180 N·cm -1 The wear rate is 0.7~1.1%.
Citation Information
Patent Citations
Liquefied petroleum gas dechlorination adsorbent and application method thereof
CN104689787A
Catalytic test paper produced by compounding bacterial cellulose-supported metal particles with plant fibers, and production method thereof
CN108543547A
High-viscosity instant carboxymethyl octenyl composite modified starch emulsifying thickener, preparation method and application thereof
CN113667026A
Dechlorinating agent as well as preparation method and application thereof
CN113952945A
Molecular sieve for dechlorination and preparation method thereof
CN115193427A
Cited By
Organic chlorine and inorganic chlorine co-removal type dechlorinating agent based on starch polysaccharide biochar and preparation method of organic chlorine and inorganic chlorine co-removal type dechlorinating agent
CN122126843A